Dampak COVID-19 Terhadap Tren Permohonan Layanan Informasi dan Pengaduan Konsumen Secara Elektronik pada ULPK Loka POM di Kabupaten Banyumas Tahun 2019-2020 - Ana Yulia; Rahmat Hidayat; Siska Indriarsih; Eka Wahyuni (Eruditio : Indonesia Journal of Food and Drug Safety, 2021)
The Consumer Complaints Service Unit (ULPK) Loka POM in Banyumas Regency is tasked with providing information, accommodating and informing the results of follow-up complaints submitted by the community. COVID-19 or better known as the Corona Virus has become a public concern and has changed the mechanism of public services at all institutions and agencies in Indonesia, including the ULPK Loka POM in Banyumas Regency. The existence of social distancing policies resulted in a change in the trend of requests for information services and consumer complaints electronically, where direct consultation facilities which in 2019 became the most popular choice of consumers (57.87%) turned into online consultations via WhatsApp as much as 52.27% in 2020. The increase in the number of WhatsApp media usage in 2020 by 13.18%. On the other hand, there was a decrease in the number of applicants in the first semester of 2021 by 22%. Through this research, it is also known that the most professions of applicants for information services and consumer complaints in 2019 were the general public (40.53%), turning into professions of business actors as much as 45.34% (2020) and 56% (Semester I of 2021). . This research was conducted using a descriptive method by analyzing data from ULPK Loka POM in Banyumas Regency which was obtained from the application of the Consumer Complaints Service Reporting System (Simpel LPK). From this study, several recommendations were obtained, namely: (1) It is necessary to carry out public service innovations for the community, (2) It is necessary to measure the Community Satisfaction Index (IKM) on a regular basis, and (3) It is necessary to determine the target focus of Communication, Information, and Education activities. (KIE) for business actors.